PENGARUH BUDAYA K3 TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH MOTIVASI KERJA (STUDI PADA RUMAH SAKIT UMUM DAERAH (RSUD) SUMBAWA) - Azri, Fadianti Waliyah (Jurnal Ilmiah Mahasiswa FEB, 2018)
The aim of this current research is to find out the influence of OSH culture on employee performance that is mediated by employee work motivation in Regional Public Hospital Sumbawa. The research design in this research is explanatory research with quantitative approach. In this research, there were 84 respondents as samples with simple random sampling technique. Method of collecting data used in this research was a questionnaire that measured with the Likert scale. Research result showed that culture of OSH has a direct significant effect towards employees' performance, the culture of OSH has a direct significant effect towards work motivation, work motivation has a direct significant effect towards employees' performance, and culture of OSH does not have a significant effect on employee performance with mediation by work motivation.Keywords: OSH, culture of OSH, work motivation, employees’ performance